Intra-week variations and associations between internal and external load measures in a elite volleyball team - Silva, D.; Vázquez, J.; Ramos, J.; Clemente, F. M.; Camões, M.; Lima, R. F. (Journal of Human Sport & Exercise, 2019)
The purpose of the present study was: (i) to analyse the variation of the internal and external load during the training days; and (ii) to analyse the levels of association between internal and external load in professional volleyball players. Eight high-level volleyball athletes participated in the study. Players used an inertial measurement unit to quantify the number and the height of the jumps made during the session. The Borg CR-10 and the session-RPE were used as internal load measures. The results indicated statistically significant differences between training days in terms of training duration, number of jumps and RPE. There were no statistically significant differences in s-RPE. There were small magnitudes correlations between internal and external loads. The present study demonstrates that the training load is variable throughout the week, with the most voluminous and intense training occurring on the second and third days before the match.